From “The Talisman of Happiness” to food design - Pozzato, Maria Pia (E|C, 2020)
Semiotics has considered the question of taste as one of its fields of research, extending its meaning from the strictly aesthetic one to the more generally aesthetic and phenomenological one, relating to the role of sensitivity in the process of establishing the effects of meaning.I will deal with cooking not so much as a cultural fact or as a technical fact but as a "hand to hand" between those who cook and the materials they deal with. The basic hypothesis is that in every age the sociosemiotic background of the production and consumption of food has also changed in the way in which subjects physically place themselves in the environment and interact with tools and materials.